Hubungan Karakteristik Masyarakat Terhadap persepsi Peneriman Vaksin Covid-19 Di Kabupaten Karawang - Syeli Syawaliyah; Indah Laily; Ahsanal Kasasiah (Jurnal Ilmiah Wahana Pendidikan, 2022)
COVID-19 is a new health problem that emerged in early 2020 which is currently threatening the world. The increasingly high prevalence of COVID-19 cases and very worrying prompted the government to issue several policies aimed at breaking the chain of transmission of COVID-19 and protecting the community from the outbreak of this COVID-19 disease. The COVID-19 vaccine is one of the most effective and economical ways to prevent infectious diseases such as COVID-19. The government has imposed a COVID-19 vaccine for all Indonesians for free. However, this vaccination policy has again caused controversy for some people. The spread of misinformation about the COVID-19 vaccine is one of the factors that affect public perception of the COVID-19 vaccine. In addition, community characteristics such as age, gender, knowledge, and so on also play a role in influencing public perceptions of the COVID-19 vaccine. From this perception, it will also influence the acceptance of the COVID-19 vaccine in the community. The purpose of this study was to determine the relationship between community characteristics and public perception of the COVID-19 vaccine in Karawang Regency. This research is a quantitative descriptive study using a cross sectional design which was carried out in Karawang Regency with a total sample of 400 people. Data analysis using Chi Square test. The results show that there is no relationship between community characteristics (age, gender, education, employment status, economic status, marital status, knowledge) on perceptions of receiving COVID-19 vaccine in Karawang Regency.